Determinants of carotid-femoral pulse wave velocity in prepubertal children - Correia-Costa, Ana; Correia-Costa, Liane; Afonso, Alberto Caldas; Schaefer, Franz; Guerra, António; Moura, Cláudia; Mota, Cláudia; Barros, Henrique; Areias, José Carlos; Azevedo, Ana (International journal of cardiology, 2016)
Abstract Background Pulse wave velocity (PWV) is a noninvasive technique to evaluate arterial stiffness, a dynamic property of the vessels, reflecting their structure and function. Childhood obesity is associated with several cardiovascular comorbidities and to the progression of atherosclerosis. We aimed to compare carotid-femoral PWV between normal weight and overweight/obese prepubertal children and to quantify its association with other cardiovascular risk factors. Methods Cross-sectional study of 315 children aged 8-9years. Anthropometrics, 24-h ambulatory blood pressure (BP) and carotid-femoral PWV were measured. Classification of obesity was according to World Health Organization (WHO) body mass index (BMI)-for-age reference values. Results Compared to normal weight children, overweight and obese children presented significantly higher levels of PWV (4.95 (P25-P75: 4.61-5.23), 5.00 (4.71-5.33), 5.10 (4.82-5.50) m/s, respectively; p trend <0.001). Significant positive correlations were found between PWV and total cholesterol, LDL cholesterol, triglycerides, fasting insulin and insulin resistance levels (HOMA-IR) and with high-sensitivity C-reactive protein (hs-CRP). In a multivariate linear regression model adjusted for sex, age, height and 24-h systolic blood pressure z-score, the independent determinants of PWV were BMI, HOMA-IR and the absence of dipping. Conclusions The association between PWV and the loss of dipping and insulin resistance levels, independently of the BMI, reinforces the contribution of these comorbidities to vascular injury in early life.
Gesehen am 05.05.2020